Europäisches Nordmeer und Barents See / Herausgegeben vom Oberkommando der Kriegsmarine 1942 - Germany. Kriegsmarine. Oberkommando; (Berlin : Oberkommando der Kriegsmarine;, 1943)
Relief shown by hachures and spot heights. Depths shown by soundings.; Includes inset map.; Selected lights shown in yellow and orange.; "Nr. 155."; West sheet with title missing; title taken from margin of middle sheet. Table of contents: [East sheet] -- [Middle sheet] Color; 1:2,000,000